The Effect of Self-Awareness and Competition on Dishonesty - Ceren Bengü Çıbık; Daniel Sgroi (Institute of Labor Economics (IZA), 2021)
We provide the first investigation of the relationship between self-awareness and dis- honesty in a multi-wave pre-registered experiment with 1,260 subjects. In the first wave we vary the level of awareness of subjects' past dishonesty and explore the impact on behaviour in tasks that include the scope to lie. In the second wave we vary the degree of competitiveness in one of our core tasks to further explore the interactions between self-awareness, (dis)honesty and competition. We also test for the experimental demand effect in order to rule it out. Our results suggest that in non-interactive tasks, self-awareness helps to lower dishonesty in the future. However, in tasks that are competitive in nature becoming more aware of past dishonesty raises the likelihood of dishonesty in the future. In other words, we show when making people aware of their own past dishonesty can help to reduce dishonesty and when it might back-fire.
Keywords: D03; D82; C91; C92; 330; lying; honesty; truth-telling; cognitive dissonance; social norms; competition; experiment